2022
DOI: 10.30630/joiv.6.1.864
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tumor Identification Based on VGG-16 Architecture and CLAHE Method

Abstract: Magnetic Resonance Imaging (MRI) in diagnosing brain cancers is widespread. Because of the variety of angles and clarity of anatomy, it is commonly employed. If a brain tumor is malignant or secondary, it is a high risk, leading to death. These tumors have an increased predisposition for spreading from one place to another. In detecting brain abnormality form such as a tumor, from a magnetic resonance scan, expertise and human involvement are required. Previous, the image segmentation of brain tumors is widely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The proposed model, which contains various layers, aims to classify MRI brain tumor The proposed model achieved higher accuracy of 97.02% and outperformed the various previous works Xinyu Lei [ 12 ] Hybrid dilated CNN Proposed a dilated CNN model, which is built by replacing the convolution kernels of traditional CNN by dilated convolution kernels, and then, the dilated CNN model is tested on the Mnist handwritten digital recognition data set The dilated CNN model reduces the training time by 12:99% and improves the training accuracy by 2:86% averagely, compared with the dilated CNN model Himanshu Padole [ 13 ] Graph CNN, graph wavelet transforms A novel two-stage graph coarsening method rooted in graph signal processing and its application in the GCNN architecture The proposed model achieved higher accuracy of 99.30% and outperformed the various previous works Sichao Fu [ 14 ] Graph-based semi-supervised learning, manifold assumption based SSL algorithms The spectral graph Hessian convolutions is a combination of the Hessian matrix and the spectral graph convolutions HesGCN can learn more efficient data features by fusing the original feature information with its structure information based on Hessian Isselmou Abd El Kader [ 15 ] differential deep-CNN differential deep convolutional neural network model to classify different types of brain tumor, including abnormal and normal MR images The experimental results showed that the proposed model achieved an accuracy of 99.25% Chirodip Lodh Choudhury [ 16 ] Extracting features through a CNN Deep neural network and incorporates a CNN based model to classify the MRI as “detected” or “not detected” The model captures a mean accuracy score of 96.08% with f-score of 97.3 Anushka Singh [ 17 ] Deep CNN The proposed deep learning method which is used to classify Brain tumor types. Our method is based on VGG16 architecture with CNN as the classifier An accuracy of above 93% along with high precision, recall and F-score was achieved Saran Raj Sowrirajan [ 18 ] VGG16 and Neural Autoregressive Distribution Estimation ...…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed model, which contains various layers, aims to classify MRI brain tumor The proposed model achieved higher accuracy of 97.02% and outperformed the various previous works Xinyu Lei [ 12 ] Hybrid dilated CNN Proposed a dilated CNN model, which is built by replacing the convolution kernels of traditional CNN by dilated convolution kernels, and then, the dilated CNN model is tested on the Mnist handwritten digital recognition data set The dilated CNN model reduces the training time by 12:99% and improves the training accuracy by 2:86% averagely, compared with the dilated CNN model Himanshu Padole [ 13 ] Graph CNN, graph wavelet transforms A novel two-stage graph coarsening method rooted in graph signal processing and its application in the GCNN architecture The proposed model achieved higher accuracy of 99.30% and outperformed the various previous works Sichao Fu [ 14 ] Graph-based semi-supervised learning, manifold assumption based SSL algorithms The spectral graph Hessian convolutions is a combination of the Hessian matrix and the spectral graph convolutions HesGCN can learn more efficient data features by fusing the original feature information with its structure information based on Hessian Isselmou Abd El Kader [ 15 ] differential deep-CNN differential deep convolutional neural network model to classify different types of brain tumor, including abnormal and normal MR images The experimental results showed that the proposed model achieved an accuracy of 99.25% Chirodip Lodh Choudhury [ 16 ] Extracting features through a CNN Deep neural network and incorporates a CNN based model to classify the MRI as “detected” or “not detected” The model captures a mean accuracy score of 96.08% with f-score of 97.3 Anushka Singh [ 17 ] Deep CNN The proposed deep learning method which is used to classify Brain tumor types. Our method is based on VGG16 architecture with CNN as the classifier An accuracy of above 93% along with high precision, recall and F-score was achieved Saran Raj Sowrirajan [ 18 ] VGG16 and Neural Autoregressive Distribution Estimation ...…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that the developed hybrid VGG16-NADE model outperforms other models in terms of accuracy, specificity, sensitivity, and the F1 score. The suggested hybrid VGG16-NADE model achieved a prediction accuracy of 96.01%, precision of 95.72%, recall of 95.64%, F-measure of 95.68%, a receiver operating characteristic (ROC) of 0.91, an error rate of 0.075, and a Matthews correlation coefficient (MCC) of 0.3564 [ 18 ].…”
Section: Related Workmentioning
confidence: 99%
“…Edge detection that gives good results requires procedures that focus on image quality settings [30]. The procedure performed before edge detection is to overcome the uneven [31], [32] contrast in the Pap smear image during acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…Image recognition and processing are very well done with Convolutional Neural Networks [5]. Training and Testing are carried out after all datasets have been collected so that the process of validating drawings can be carried out [6].…”
Section: Introductionmentioning
confidence: 99%